Relevant Measures to Prevent the Spread of African Swine Fever in the European Union Domestic Pig Sector - Jurado, Cristina; Martínez-Avilés, Marta; De La Torre, Ana; Štukelj, Marina; de Carvalho Ferreira, Helena Cardoso; Cerioli, Monica; Sánchez-Vizcaíno, José Manuel; Bellini, Silvia (Frontiers in Veterinary Science, 2018)
During the last decade, African swine fever (ASF) has spread from the Caucasus region to eastern European Union (EU) countries affecting domestic pig and wild boar populations. In order to avert ASF spread, mitigation measures targeting both populations have been established. However, despite these efforts, ASF has been reported in thirteen different countries (Georgia, Azerbaijan, Armenia, the Russian Federation, Ukraine, Belarus, Estonia, Latvia, Lithuania, Poland, Moldova, Czech Republic and Romania). In the absence of an effective vaccine or treatment to ASF, introduction and spread of ASF onto domestic pig farms can only be prevented by strict compliance to control measures. This study systematically reviewed available measures to prevent the spread of ASF in the EU domestic pig sector distinguishing between commercial, non-commercial and outdoor farms. The search was performed in PubMed and using a common browser. A total of 52 documents were selected for the final review process, which included scientific articles, reports, EU documents and official recommendations, among others. From this literature review, 37 measures were identified as preventive measures for the introduction and spread of ASF. Subsequently, these measures were assessed by ASF experts for their relevance in the mitigation of ASF spread on the three mentioned types of farms. All experts agreed that some of the important preventive measures for all three types of farms were: the identification of animals and farm records; strict enforcement of the ban on swill feeding; and containment of pigs, so as to not allow direct or indirect pig - pig and/or pig - wild boar contacts. Other important preventive measures for all farms were education of farmers, workers and operators; no contact between farmers and farm staff and external pigs; appropriate removal of carcasses, slaughter residues, and food waste; proper disposal of manure and dead animals, and abstaining from hunting activities during the previous 48 hours (allowing a 48 hour interval between hunting and being in contact with domestic pigs). Finally, all experts identified that the important preventive measures for non-commercial and outdoor farms, is to improve access of those farms to veterinarians and health services.